Genetic Signatures of Selection for Cashmere Traits in Chinese Goats - Meilin Jin; Jian Lu; Xiaojuan Fei; Zengkui Lu; Kai Quan; Yongbin Liu; Mingxing Chu; Ran Di; Huihua Wang; Caihong Wei (Animals, 2020)
Inner Mongolia and Liaoning cashmere goats in China are well-known for their cashmere quality and yield. Thus, they are great models for identifying genomic regions associated with cashmere traits. Herein, 53 Inner Mongolia cashmere goats, Liaoning cashmere goats and Huanghuai goats were genotyped, and 53,347 single-nucleotide polymorphisms (SNPs) were produced using the Illumina Caprine 50K SNP chip. Additionally, we identified some positively selected SNPs by analyzing Fst and XP-EHH. The top 5% of SNPs had selection signatures. After gene annotation, 222 and 173 candidate genes were identified in Inner Mongolia and Liaoning cashmere goats, respectively. Several genes were related to hair follicle development, such as TRPS1, WDR74, LRRC14, SPTLC3, IGF1R, PADI2, FOXP1, WNT10A and CSN3. Gene enrichment analysis of these cashmere trait-associated genes related 67 enriched signaling pathways that mainly participate in hair follicle development and stem cell pluripotency regulation. Furthermore, we identified 20 overlapping genes that were selected in both cashmere goat breeds. Among these overlapping genes, WNT10A and CSN3, which are associated with hair follicle development, are potentially involved in cashmere production. These findings may improve molecular breeding of cashmere goats in the future.